THE EFFECT OF HYPNOPARENTING TECHNIQUES GIVING POSITIVE SUGGESTION ON THE DEVELOPMENT OF CHILDREN IN BEHAVIOR RESPONSIBILITY TO PRE-SCHOOL CHILDREN - VERI VERI; SRI SUPAMI; RITA DWI PRATIWI; SAFITRI RAHAYU (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACTAccording to WHO (2017), as many as 35-50% of preschool age children experience delays in their development, in the scope of development alone about 5-25% experience general developmental delays or global developmental delays. According to the Indonesian Ministry of Health Based on the results of child development screening conducted in 30 provinces, it was found that 45% of Indonesian toddlers had developmental disorders, both fine and gross motor development, social independence, lack of intelligence and delays. The purpose of this study was to determine the effect of the Hypnoparenting technique by giving positive suggestions to the development of children in being responsible for pre-school children at RA Nurul Falah Cigombong. This research method is a quantitative research with an experimental approach with the aim of knowing the effect between the independent variable and the dependent variable, in the form of the one group pretest-posttest design. The number of samples was 30 students RA Nurul Falah Cigombong. From the research results of the study obtained before the Hypnoparenting technique was carried out Most of the respondents had a bad attitude of responsibility 24 respondents (80%), while after the Hypnoparenting technique was carried out Most of the respondents had a good attitude of responsibility development as many as 23 respondents (76.7%). This study used the Wilcoxone test with a significance degree of p<0.05 (5%). The results of the statistical test obtained a value of (0.000), so it can be concluded that there is an effect of Hypnoparenting technique of giving positive suggestions to the development of children in being responsible for preschool children at RA Nurul Falah Cigombong. Suggestions from the results of this study are expected to provide one recommendation for agency programs to carry out a community service using Hypnoparenting techniques with child targets.Keywords: Attitude of Responsibility, Hypnoparenting PENGARUH TEKNIK HYPNOPARENTING PEMBERIAN SUGESTI POSITIF TERHADAP PERKEMBANGAN ANAK DALAM BERSIKAP TANGGUNG JAWAB PADAANAK PRA SEKOLAH ABSTRAKMenurut WHO (2017), sebanyak 35-50% anak usia prasekolah mengalami keterlambatan dalam perkembangannya, pada cakupan perkembangan saja sekitar 5-25% yang mengalami keterlambatan perkembangan umum atau global developmental delay. Menurut Kemenkes Indonesia Berdasarkan hasil skrining perkembangan anak yang dilakukan pada 30 provinsi didapatkan sebanyak 45% balita Indonesia mengalami gangguan perkembangan, baik perkembangan motorik halus dan kasar, sosial kemandirian, kecerdasan kurang dan keterlambatan. Tujuan penelitian ini adalah untuk mengetahui pengaruh teknik Hypnoparenting pemberian suggesti positif terhadap perkembangan anak dalam bersikap tanggung jawab pada anak pra sekolah di RA Nurul Falah Cigombong. Metode penelitian ini merupakan penelitian kuantitatif dengan pendekatan eksperimen dengan Tujuan untuk mengetahui pengaruh antara variabel independen dengan variabel dependen, dalam bentuk the one group pretest-posttest design. Jumlah sampel sebanyak 30 siswa RA Nurul Falah Cigombong. Hasil penelitian diperoleh sebelum dilakunan teknik Hypnoparenting Sebagian besar responden memiliki sikap tanggung jawab kurang baik 24 responden (80%), sedangkan setelah dilakukan teknik Hypnoparenting Sebagian besar responden memiliki perkembangan sikap tanggung jawab baik sebanyak 23 responden (76,7%). Penelitian ini menggunakan uji wilcoxone dengan derajat kemaknaan p0.05 (5%). Hasil uji statistik didapatkan nilai (0.000). Kesimpulan bahwa ada pengaruh teknik Hypnoparenting pemberian suggesti positif terhadap perkembangan anak dalam bersikap tanggung jawab pada anak pra sekolah di RA Nurul Falah Cigombong. Saran dari hasil penelitian ini diharapkan memberikan salah satu rekomendasi terhadap program instansi untuk melakukan sebuah pengabdian masyarakan dengan menggunakan teknik Hypnoparenting dengan target sasaran anak.Kata kunci: Hypnoparenting, Sikap Tanggung Jawab